Relative QoS optimization for multiparty online gaming in DiffServ networks. - Lei Liang (IEEE Communications magazine)
Real-time interactive multimedia multiparty communication is becoming a vital part of modern Internet services. As one of its applications, online gaming attracts a huge group of fans playing over the Internet. It has new requirements for relative QoS. This article gives a brief introduction to these new QoS requirements, and then presents an algorithm to satisfy these requirements in the differentiated services network for client-server-topology-based online gaming services. Our simulation results show that this algorithm can provide optimized relative QoS support for online gaming as an example of multiparty communications.